Factors influencing audit findings of the Indonesian district governments' financial statements - Bambang Pamungkas; Cendy Avrian; Reisya Ibtida (Cogent Business & Management, 2019)
The Regional Governments' Financial Statements in Indonesia that have obtained unqualified opinions had increased in recent years. However, the audit findings on the local government's financial reports have also increased. Those conditions have motivated us to empirically analyze the factors that influence the increasing number of audit findings in district governments in Indonesia for the 2016 and 2017 fiscal years. The independent variables are the Size of the Regional Government, Local Income, Capital Expenditures, and Follow-Up of Audit Recommendations. We measure their influence on the Non-Compliance with Regulations using the Weaknesses of the Internal Control System as the moderating variable. Our results show that Size has a positive impact on the Internal Control System. Otherwise, the Completion of Audit Recommendation negatively affects both the Internal Control System and the Non-Compliance with Regulatory. The other independent variables of Local Income and Capital Expenditures did not show any influence on the number of audit findings. Simultaneously, Size, Local Income, Capital Expenditures, and Follow-Up of Audit Recommendation have an indirect relationship to Non-Compliance with Regulation findings through Internal Control System Weaknesses. Our research emphasizes the importance of developing a comprehensive internal control system for local governments, along with the improvement of asset governance. Moreover, we also encourage the completion of audit recommendations on local governments to avoid the reoccurrence of similar findings.
Keywords: 650; government audit; internal control system; compliance to regulations; size of the regional government; local income; capital expenditures; follow-up of audit recommendations